Anaplastic thyroid carcinoma with leucocytosis - Naeem, Shagufta; Riyaz, Anila; Naz, Shabana; Jamil, Aisha; Rehman, Abdur; Maqbool, Sidra; Javed, Hamza (Journal of Ayub Medical College Abbottabad, 2021)
Background: Anaplastic thyroid carcinoma is a high-grade tumour with poor prognosis. Most of the cases are easily diagnosed on cytology and some of these are associated with increased neutrophils in cytology specimen as well as in the blood. The objective of the study is to determine the frequency of neutrophilia with fever in anaplastic thyroid carcinoma. Methods: This descriptive cross-sectional study was performed in the Department of Pathology Ayub Teaching Hospital Abbottabad as well as in association with Advance lab Abbottabad. All the cases diagnosed as anaplastic thyroid carcinoma on cytology were included, histopathological examination was done only in 5 cases. The duration of study was from October 2016 to October 2019 were included in the study. Results: Out of 150 cases of thyroid cytology 09 were diagnosed as anaplastic thyroid carcinoma. The mean age of patients was 65.7±6.96. Gender distribution was 5/9 (55.6%) males and 4/9 (44.4%) were females. Out of which 05 were confirmed on histopathology 3 patients died within a month and 1 patient refused a biopsy. All of these cases were associated with an increased number of neutrophils on cytology and WBC count is 04 cases showed leucocytosis. All of them presented with rapidly growing mass in long-standing goitre with a median duration of 2 months. Weight loss was seen in 4/9 (44.44%), 3/9 (33.33%) presented with hoarseness of voice while only 1/9 (11.1%) patient presented with superior vena caval syndrome. Conclusion: In long-standing goitre rapid increase in size with fever and leucocytosis are suggestive of anaplastic thyroid carcinoma which should be investigated promptly. Keywords: Anaplastic thyroid carcinoma; leucocytosis; Goitre